Fiber Bragg grating as UVA sensor - Lesiak, Piotr; Widomski, Adam; Szelągowski, Łukasz; Sobotka, Piotr; Dużyńska, Anna; Wróblewska, Anna; Markowski, Konrad; Osuch, Tomasz; Woliński, Tomasz (Photonics Letters of Poland, 2018)
The idea of this paper implies the possibility to exploit the properties of graphene oxide (GO) to fiber Bragg grating (FBG) UVA radiation sensor design. The idea assumes that a temperature change around the fiber can be induced by UVA radiation. UVA lighting will increase the internal energy of the GO and consequently locally raise the temperature on the surface of the optical fiber with FBG sensor and changing Bragg wavelength Full Text: PDF References Z. N. Azwa, B. F. Yousif, A. C. Manalo, W. Karunasena, " A review on the degradability of polymeric composites based on natural fibres", Materials & Design, Vol. 47, pp. 424-442, 2013 CrossRef B. R?nby, "Photochemical modification of polymers - photocrosslinking, surface photografting, and lamination", Polymer Ing. & Science, Vol. 38, Iss. 8, pp 1229-1243, 1998 CrossRef P. Lesiak, M. Szeląg, D. Budaszewski, R. Plaga, K. Mileńko, G. Rajan, Y. Semenova, G. Farrell, A. Boczkowska, A. Domański, T. Woliński, "Influence of lamination process on optical fiber sensors embedded in composite material", Measurement: Journal of the International Measurement Confederation, vol. 45, No. 9, pp. 2275-2280, 2012 CrossRef G. Eda et al., "Large-area ultrathin films of reduced graphene oxide as a transparent and flexible electronic material", Nature Nanotechnology 3, 270 (2008) CrossRef H. J. Kim et al., "Unoxidized Graphene/Alumina Nanocomposite: Fracture- and Wear-Resistance Effects of Graphene on Alumina Matrix", Scientific Reports 4, 5176 (2014) CrossRef A. Wróblewska et al., "Statistical analysis of the reduction process of graphene oxide probed by Raman spectroscopy mapping", Journal of Physics: Condensed Matter 29, 475201 (2017) CrossRef P. Lesiak, P. Sobotka, M. Bieda, A. Dużyńska, A. Wróblewska, M. Chychłowski and T. R. Woliński, "Innovative UV sensor based on highly birefringent fiber covered by graphene oxide", Photonics Letters of Poland Vol. 7, No 4, pp. 124-126, 2015 CrossRef B. Qi, M. Bannister, X. Liu, A. Michie, L. Rajasekera, B. Ashton, Response of an embedded fibre Bragg grating to thermal and mechanical loading in a composite laminate, IOME Australasia, Materials Forum 27 (2004) 93?100. DirectLink E. Chehura, C-C. Ye, S. Staines, S. James, R. Tatam, Characterisation of the response of fibre Bragg gratings fabricated in stress and geometrically induced high birefringence fibres to temperature and transverse load, Smart Materials and Structures 13 (2004) 888?895. CrossRef K. Schroeder et al., A fiber Bragg grating sensor system monitors operational load in a wind turbine rotor blade, Measurement Science & Technology 17 (2006) 1167?1172. CrossRef Z. Zhou, Q. Liu, Q. Ai, C. Xu, Intelligent monitoring and diagnosis for modern mechanical equipment based on the integration of embedded technology and FBGS technology, Measurement 44 (9) (2011) 1499?1511 CrossRef Z. C. Wu et al., Science 305, 1273 (2004) CrossRef A. Jorio, M. Dresselhaus, R. Saito, and G. F. Dresselhaus, Raman Spectroscopy in Graphene Related Systems (Wiley-VCH, 2011) CrossRef G. Sobon, J. Sotor, J. Jagiello, R. Kozinski, M. Zdrojek, M. Holdynski, P. Paletko, J. Boguslawski, L. Lipinska, and K. M. Abramski "Graphene Oxide vs. Reduced Graphene Oxide as saturable absorbers for Er-doped passively mode-locked fiber laser" Optics Express 20, 19463 (2012) CrossRef